2010
DOI: 10.4301/s1807-17752010000300003
|View full text |Cite
|
Sign up to set email alerts
|

THE PREDICTORS OF SUCCESS FOR E-LEARNING IN HIGHER EDUCATION INSTITUTIONS (HEIs) IN N-W.F.P, PAKISTAN

Abstract: One cannot predict the details of future but one can surely prepare for it. Researchers in eLearning are capitalizing on the user-perceptions as possible predictor of the userattitudes towards the development, use, problems and prospects of eLearning in their institutions. This application is founded on the psychological fact that a human's attitude depends on his/her ‗belief' or ‗perceptions: meaning given by the individual' about the thing used. That is, if eLearning users perceive educational technologies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 16 publications
0
19
0
4
Order By: Relevance
“…We have found that little work has been done in this area of research in Pakistan. Some studies have been conducted for Pakistan such as (Farid, Ahmad, Niaz, Itmazi, & Asghar, 2014;Iqbal & Ahmed, 2010;Kundi, Nawaz, & Khan, 2010;Nawaz, 2012;Qureshi et al, 2012;Qureshi, Nawaz, & Khan, 2011), but these studies have identified only some of the e-learning challenges, issues or predictors but no classification of the issues have been performed. Moreover, according to our knowledge, no such study have been conducted which have not only identified but also classified and prioritized the issues for the promotion of e-learning in Pakistan.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have found that little work has been done in this area of research in Pakistan. Some studies have been conducted for Pakistan such as (Farid, Ahmad, Niaz, Itmazi, & Asghar, 2014;Iqbal & Ahmed, 2010;Kundi, Nawaz, & Khan, 2010;Nawaz, 2012;Qureshi et al, 2012;Qureshi, Nawaz, & Khan, 2011), but these studies have identified only some of the e-learning challenges, issues or predictors but no classification of the issues have been performed. Moreover, according to our knowledge, no such study have been conducted which have not only identified but also classified and prioritized the issues for the promotion of e-learning in Pakistan.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, the authors have emphasized on the implementation level rather than promotion of the e-learning. Another effort has been made by Kundi et al (2010), highlighting the predictors of success for the e-learning. The authors discovered lack of user training, underestimation, lack of awareness, lack of technical and administrative end-user support and resistance to change as some of the users' problems in e-learning.…”
Section: Introductionmentioning
confidence: 99%
“…Vprašalnik smo oblikovali na podlagi pregleda izvirnih znanstvenih člankov (Keller & Cernerud, 2002;Docherty & Sandhu, 2006;Borstorff & Lowe, 2007;Mitchell, et al, 2007;Yaghoubi, et al, 2008;Dwyer & Reid-Searle, 2009;Kundi, et al, 2010;Moule, et al, 2010;Dosari, 2011;Lin, et al, 2011;Bristol & Kyarsgaard, 2012;Muhammad Umar & Choudhary Zahid, 2012;Ličen, 2013) v mednarodnih bazah podatkov CINAHL in ProQuest ter vzajemni bibliografski-kataložni bazi podatkov COBIB.SI. Sestavljen je iz demografskih podatkov (letnik študija, obvezna prisotnost v e-učilnici, izkušnje z e-učilnico, stil učenja, podpora skupinskega/ individualnega dela) in treh vsebinskih sklopov z uporabo 5-stopenjske Likertove lestvice, in sicer: odnos študentov do e-izobraževanja, pričakovanja in prednosti e-izobraževanja (1 -se sploh ne strinjam, 2 -se ne strinjam, 3 -neopredeljen, 4 -se strinjam, 5 -popolnoma se strinjam).…”
Section: Opis Instrumentaunclassified
“…Zadovoljstvo z e-izobraževanjem se lahko v 57 % pojasni z odnosom do IKT, s podporo učitelja, razvojem e-izobraževanja in uporabo e-učilnice (Kundi, et al, 2010;Lin, et al, 2011). V naši raziskavi nismo ugotovili bolj pozitivnega odnosa do e-izobraževanja med študenti z obvezno prisotnostjo v e-učilnici kot med študenti brez obvezne prisotnosti.…”
Section: Diskusijaunclassified
“…technical, pedagogical, personnel), as facilitating circumstance, has an important impact on applying e-learning in education (Timothy, 2009). Availability of information about the manner of applying e-learning technology in education process can positively influence teacher's adoption of e-learning (Kundi et al, 2010). Since introduction of e-learning technology into academic institutions causes changes in structure, policies and organizational culture, it also brings about changes in organizational learning.…”
Section: Institutional Factorsmentioning
confidence: 99%